(untitled) (Journal of Environmental Science Studies, 2018)
To produce biodiesel from waste oil and use it as an alternative fuel in compression ignition (CI) engines is an efficient way to eliminate this harmful compound. In this experimental study, the effects of biodiesel derived from waste oil on emission and performance characteristics of CI engine were investigated. The production of biodiesel was realized at the condition: 9wt% acid catalyst amount, 9:1 molar ratio, 60oC reaction temperature and 120min reaction time. Biodiesel and diesel were mixed with different volumetric ratios and the properties of each blend were analyzed. Each blend was tested with a direct injection CI engine to see the effect of biodiesel on performance and emission characteristics. In conclusion, blends showed similar results in terms of performance comparing to diesel. The use of biodiesel derived from waste oil led to decrease in hydrocarbon (HC), carbon monoxide (CO) emissions and smoke opacity up to 81.25%, 55.02% and 40.48% respectively while led to slight increase in nitrogen oxides (NO ) emissions in general. x